Mental health in adolescents after experiencing a flood event in Bavaria, Germany—A qualitative interview study - Schürr, Alina; Elbel, Johanna; Hieronimi, Annika; Auer, Isabel; Coenen, Michaela; Böse-O'Reilly, Stephan (Frontiers in Public Health, 2023)
Background Children and adolescents are particularly vulnerable to the mental health impacts of extreme weather events (EWEs). This qualitative study aims to explore the stressful and protective factors after experiencing an EWE, such as flooding, how adolescents coped with these experiences and what mental health care they received.Methods Nine semi-structured interviews were conducted with young adults (18-24 years) living in Simbach am Inn, a German town affected by flooding in 2016. The interviews were analyzed using Kuckartz's qualitative content analysis.The days after the flood were described as the most stressful time. The main stressors were concern for their family, confrontation with the extent of the damage and uncertainty during the flood. In terms of protective factors, respondents cited talking about the flood, family support and helping with cleanup as the most important. Adolescents requested further mental health care in schools and not just in the immediate aftermath.Future preventive and therapeutic care measures should be optimized according to protective and stressful factors. Mental health care should be offered after months and should be low-threshold. Additionally, the social environment of adolescents is essential for their mental well-being after an EWE and needs to be strengthened.